Pengaruh Penerapan Absensi Biometrik Terhadap Tunjangan Kinerja Dan Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Tulungagung - Retnawati, Dyah; Mutiara, Nisa (Otonomi, 2024)
The purpose of this research is to analyze the impact of biometric attendance on worker support and performance at Tulungagung district education service. This research uses descriptive quantitative methods. With the entire population of 461 being in the shade of the education service Tulungagung district. There for a research sample using a Slovin technique it was obtained by as many as 82 responders used in this research. Field observation and literature method. Meanwhile the data analysis uses linier regression analysis. The result of this research show that biometric has a positive effect on benefits. Supported by F a count of 48,280 with a sig value 0.000. It sows that F a count are greater than F table or 48.280 > 3.96 with a sig value 0.000 < 0.05. in addition the t count 6.948 > t table 1.665, so it can be concluded that hypothesis accepted. Which means that biometric impact on the work. While in the employee performance of known values F count is 80.971 an the sig value 0.000. Those showing that the F count 80.971 > F table 3.96 with the sig < 0.05. Then t count 8.998 of biometric. Because te value of t count 8.998 > t table 1.655. that’s way, it can be concluded that hypothesis accepted. Which means that for biometric attendance influences the employee performance.